(untitled) (Medical Forum Monthly, 2024)
Objective: This study aimed to observe the hematological side effects of sofosbuvir and ribavirin therapy in treatment of chronic hepatitis C (CHC) patients. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Outpatient Department of Gastroenterology, Nishtar Hospital Multan from October 2016 to March 2017. Materials and Methods: It included 117 treatment naive patients with CHC who were given combination therapy of Sofosbuvir and ribavirin. Patients complete blood picture was sent at the baseline and then repeated at 1 month and at 3 months. Drop in mean of all blood parameters was calculated. Cut-off for Significant Side effects were set as follows: Anemia (Hb<10gm/dL), Leukopenia (<4000 WBCs/mm3), Thrombocytopenia (<100,000 platelets/mm3). Data was analyzed using the SPSS version 17. Results: Out of 117 patients, 64 (54.7%) were females and 53 (45.3%) were males. Mean age of patients was 39.28 ± 11.23 years. Mean hemoglobin (Hb), total leukocyte count (TLC) and platelets (PLT) before treatment were 12.51 g/dL, 8.53 x103 /mcL and 273 x103 /mcL, respectively. Mean Hb and TLC kept on decreasing as the treatment progressed. The decrease in mean of WBC was statistically significant (p<0.001). Mean platelet count increased at 1 month and decreased at 3 months. Significant side effects were observed as follows: anemia was seen in only 3.4% patients, leukopenia in 2.6% patients and thrombocytopenia in 0.8% patients. Conclusion: Hematological abnormalities are uncommon in sofosbuvir and ribavirin therapy